An electrochemical aptasensor for detection of bovine interferon gamma. Issue 31 (21st July 2017) - Crulhas, Bruno P.; Hadley, Dustin; Liu, Ying; Shin, Dong-Sik; Stybayeva, Gulnaz; Imanbekova, Meruyert; Hill, Ashley E.; Pedrosa, Valber; Revzin, Alexander
Abstract : Bovine tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB) in which it is hard to identify the pathological symptoms. Abstract : Bovine tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB) in which it is hard to identify the pathological symptoms. Release of bovine interferon gamma (BoIFN-γ) by T-cells provides an important diagnostic marker of MTB infections. In this work, we developed for the first time an electrochemical aptasensor for sensitive and specific determination of BoIFN-γ. A thiolated IFN-γ-binding aptamer was conjugated with methylene blue (MB) and immobilized on a gold electrode by self-assembly. Binding of IFN-γ to the electrode surface caused a conformational change in the aptamer, decreasing electron transfer efficiency. The redox current was quantified using square wave voltammetry (SWV) and was found to be specific for bovine IFN-γ with detection limit of 0.1 nM in pristine buffer and 0.9 nM in blood. The biosensor described here may, in the future, be used for on-site testing of bovine blood to help better identify and contain outbreaks of bovine TB.